Conceptualization of Maslahah and Social Ecology In The Kromojati Tradition In Bohol Village, Gunungkidul Regency - Yuskhi, Azmul Hariz; Fiqhiyatul Khakimah (Muhammadiyah University of Surabaya, 2025)
This article discusses the concepts of maslahah and social ecology in relation to the practice of kromojati tradition in Bohol Village, Gunungkidul Regency. This study is motivated by the practice of kromojati tradition, which is a process carried out by both prospective spouses before getting married by giving 10 teak tree seedlings to the village. This raises the issue of how Islamic law, which is rahmatan lil 'alamin, can be harmonized with local customs and how traditional social structures correlate with the process of maintaining ecological systems. This type of research was field research using a phenomenological and conceptual approach. The results of this study showed that the kromojati tradition was categorized as maslahah mursalah because it was not explicitly mentioned in the text, but was in line with the objectives of sharia. This tradition was considered maslahah hajiyyah because it provided social convenience and brings collective benefits to the community. This tradition confirms that ecological solutions were effective when linked to social change and community participation. The novelty of this study is interdisciplinary integration of Islamic legal theory (maslahah) and Murray Bookchin’s theory of social ecology to analyze a local marriage tradition as an ecological and social instrument. Keywords: Conceptualisation, Maslahah, Social ecology, Kromojati.